Predicting telemedicine system user satisfaction in sub-Saharan Africa - Thierry O.C. Edoh; Ahmed Dooguy Kora; Pravin Pawar; G. Christine Coulibaly; Bidossessi R.U. Alahassa (ICT Express, 2016)
During our literature review and on-site research in developing countries, particularly in Sub-Saharan Africa, we could not point out any efforts to measure the Quality of Service (QoS) and Quality of Experience (QoE) provided by telemedicine systems, thus making it impossible to understand their overall levels of user satisfaction in sub-Saharan African countries. Therefore, we conducted a qualitative and quantitative study, with experiments to measure QoS performance and the end-user QoE perception of telemedicine systems. Based on obtained results, we propose a mathematical formula to predict the QoE based on QoS measurement values, since a known relationship exists between QoS and QoE.